A temporal object relational SQL language with attribute timestamping in a temporal transparency environment - Chau, Vo Thi Ngoc; Chittayasothorn, Suphamit (My University, 2008)
In this paper, a temporal object relational SQL language is proposed. It is intended to facilitate the non-procedural data definitions, queries, and modifications of temporal databases with attribute timestamping in a temporal transparency environment. With attribute timestamping, temporal data of any type is naturally handled. With temporal logic, users can issue temporal queries in an intuitively expressive manner. The language provides valid time support for upward compatibility, temporal upward compatibility, sequenced and non-sequenced variants to serve both non-temporal and temporal users. Using object relational technology, the implementation is made for embedded and interactive SQL modes. All existing interfaces of an ORDBMS are inherited with temporal transparency. © 2008 Elsevier B.V. All rights reserved.
Keywords: Attribute timestamping; Object relational database; SQL; Temporal database; Temporal transparency